Charles Burnett and Dorian Gieseler Greenbaum (eds.), From M?sh??all?h to Kepler: Theory and Practice in Medieval and Renaissance Astrology - Carey, Hilary M. (Journal for the Study of Religion, Nature and Culture, 2019)
Charles Burnett and Dorian Gieseler Greenbaum (eds.), From M?sh??all?h to Kepler:Theory and Practice in Medieval and Renaissance Astrology (Ceredigion, Wales: SophiaCentre Press, 2015), 529 pp., £35.00 (pbk), ISBN: 978-907767-06-7.